Electroreduction of oxygen in alkaline solution on iron phthalocyanine modified carbide-derived carbons. (10th March 2019) - Praats, Reio; Kruusenberg, Ivar; Käärik, Maike; Joost, Urmas; Aruväli, Jaan; Paiste, Päärn; Saar, Rando; Rauwel, Protima; Kook, Mati; Leis, Jaan; Zagal, José H.; Tammeveski, Kaido
Abstract: Carbide-derived carbons (CDC) are porous carbon materials with tunable pore structure, very high specific surface area and of great potential for electrochemical applications. In this work CDC-supported transition metal macrocyclic electrocatalysts are prepared using two different type of CDC materials and iron phthalocyanine (FePc). Herein, we report the superior electrocatalytic properties of FePc/CDC catalysts fabricated via simple pyrolysis approach. The morphology, composition and structural features of these CDC-based non-noble metal catalysts are evaluated using scanning and transmission electron microscopies, X-ray photoelectron spectroscopy, N2 physisorption and X-ray diffraction analysis. The electrochemical oxygen reduction reaction (ORR) behavior of FePc/CDC catalysts is evaluated employing the rotating disk electrode (RDE) method. FePc modified CDC materials demonstrate a superior ORR electrocatalytic activity in alkaline conditions, showing onset potential of −0.05 V (vs. SCE) close to that of commercial Pt/C. Thus, the RDE results show great potential of these non-Pt catalysts as cathode materials in metal-air batteries and alkaline membrane fuel cells. Graphical abstract: Image 1091 Highlights: Carbide-derived carbon (CDC) materials are modified with iron phthalocyanine (FePc). Two CDC materials with different specific surface area and porosity are used as supports. FePc/CDC catalysts are characterized by SEM, TEM, XPS, XRD and the BET method. FePc/CDC catalysts show excellent activity towards the ORR in alkaline conditions. FePc/CDC materials are promising cathode catalysts for alkaline membrane fuel cells.